Prevalence of gingivitis and associated factors among students from the Autonomous University of Guerrero, Mexico - Norma Samanta Romero Castro; Sergio Paredes Solís; José Legorreta Soberanis; Salvador Reyes Fernández; Miguel Flores Moreno; Neil Andersson (Editorial Ciencias Médicas, 2016)
Introduction: gingivitis is the most common periodontal disease. The most effective prophylactic measure against this condition is oral hygiene. Objectives: estimate the prevalence of gingivitis and identify associated risk factors among first year university students. Methods: across-sectional study was conducted from September to December 2012 based on a survey applied to 1 387 students from the Autonomous University of Guerrero in Acapulco, Mexico. Sample size was not estimated because all the students registered were surveyed. The data collection tools used were a self-applied questionnaire, oral examination forms, the simplified Green and Vermillion oral hygiene index, and the simplified Löe and Silness plaque and gingivitis indices. Gingivitis was diagnosed with values on Löe and Silness indices, where scores from 0 to 0.09 were considered healthy. The result variable studied was gingivitis. Cause variables were dental plaque, poor oral hygiene, tartar, detritus, diastema, orthodontic appliances, dental crowding and cervical wear. Results: prevalence of gingivitis estimated by school cluster was 74.5 %, of which 62.8 % was mild, 11.5 % was moderate and 0.2 % was severe. According to the Green and Vermillion index, 16 % of the students had poor hygiene, and according to the Löe and Silness indices 87.3 % had plaque. Adjustment by clusters and other variables revealed four factors associated with gingivitis: poor oral hygiene (OR 2.58; CI 95 %; 1.32-5.05), detritus (OR 2.62; CI 95 %; 1.49-4.58), diastema (OR 1.72; CI 95 %; 1.13-2.64) and cervical wear (OR 0.49; CI 95 %; 0.24-1.00). Conclusions: prevalence of gingivitis was found to be within the range reported by other studies. Poor oral hygiene, detritus and diastema were the risk factors associated with gingivitis.